Left ventricular end-systolic pressure-volume relation: A combined radionuclide and hemodynamic study - Iskandrian, Abdulmassih S.; Hakki, A-Hamid; Bemis, Charles E.; Kane, Sally A.; Boston, Barbara; Amenta, Angelo (The American journal of cardiology, 1983)
This study examines the effect of increasing heart rate by atrial pacing on the left ventricular endsystolic pressure-volume relation and determines whether peak pressure can be used instead of end-systolic pressure. Measurements were made of cardiac output (by thermodilution), pulmonary arterial pressure, ejection fraction (by radionuclide angiography), and aortic pressure (by intraarterial catheter). End-systolic pressure was measured at the dicrotic notch. The end-diastolic and end-systolic volumes were determined from the ejection fraction and cardiac output. There was excellent correlation in pressure-volume relation determined by peak pressure and end-systolic pressure (r = 0.95). In 8 normal subjects there was < 5% change in ejection fraction, a decrease in end-systolic volume, ≥ 30% increase in end-systolic pressure/ end-systolic volume, and no change in pulmonary arterial pressure with pacing. Of 20 patients with coronary artery disease, 9 patients had ≥ 5% decrease in ejection fraction, 6 had an increase in end-systolic volume, and 14 had < 30% increase in end-systolic pressure/end-systolic volume with pacing (p < 0.05). Thus (1) peak systolic pressure can be used reliably instead of end-systolic pressure; (2) atrial pacing has a positive inotropic effect in normal subjects—the minimal increase (30%) in end-systolic pressure/end-systolic volume is similar to the increase (35%) reported during exercise; (3) abnormal changes in end-systolic pressure/end-systolic volume in coronary artery disease are more common than changes in either ejection fraction or end-systolic volume with atrial pacing.